Inflation preventive problems for depositors who move savings to other banks - Muhammad Mirhan Ramadha (Gema Wiralodra, 2023)
The issue of global recession also affects the banking sector. Amid potential inflation, many depositors are being offered higher interest rates by other banks, so they are tempted to transfer their savings. The research method used in this research is normative juridical. The research results show that the banking practice of offering high-interest rates to depositors amidst issues of inflation and recession will, of course, have an impact on the stability of the banking economy.